Planet middle school : helping your child through the peer pressure, awkward moments & emotional drama - Leman, Kevin (Grand Rapids, MI : Revell, 2015)
It happens to every parent. One day, you have a sweet son or daughter who loves to snuggle on the couch and who puts a smile on your face just by walking into the room. The next day, it's as if someone left the door open and let in an alien with a smart mouth and an attitude that, frankly, you could do without. Entering middle school is like stepping onto a different planet -- for parent and child alike. But these years don't have to create chaos in your family. In fact, they can be some of the best, most fruitful years of all, a time when you can grow closer rather than drift apart. From the internal storms of hormonal changes to the external challenges of peer pressure and our technology-saturated culture, your child is under constant bombardment. Learn how to come alongside your middle-schooler with the love, understanding, and values that will see you both safely back home to earth when your time on Planet Middle School is over. Kevin Leman shows you how to understand your child's rapidly expanding world; respond rather than react to mood swings; tell your child about sex (before someone else tells their version); create opportunities for your child to practice selflessness and gratitude; ensure that your kid is one who loves home and family; and much more.
Creature from the black lagoon -- Their expanding universe -- All flared up! -- Survival of the fittest -- Walking on polar ice -- Confronting the black hole : technology at warp speed -- Growing up way too fast -- Becoming a (gulp) man/woman -- Blue chip or penny stocks? -- Understanding who your kid really is -- How to talk so they'll listen -- Expect the best, get the best -- Raising a "home" boy/girl -- Life-mapping -- Creating an attitude of gratitude -- Raising a giver in a gimme generation -- A word of encouragement -- Conclusion -- A middle-schooler's 10 commandments to parents -- Notes -- About Dr. Kevin Leman -- Resources by Dr. Kevin Leman.
Includes bibliographical references.
Keywords: Middle schools -- United States; Middle school students -- United States; Middle schools -- United States